Pembelajaran Aplikasi Microsoft Powerpoint untuk Menambahkan Audio dan Video pada SMP Swasta Citra Harapan - Dian Mayasari; Wulan Dari; Sofyan Roni (Fakultas Teknik Universitas Cenderawasih, 2025)
This training aims to enhance the skills of students at SMP Swasta Citra Harapan in using Microsoft PowerPoint, particularly in adding audio and video elements to presentations. These skills are crucial for creating more interactive and engaging presentations for the audience. Through a practical approach, this training provides both basic knowledge and advanced techniques in inserting, editing, and managing audio and video on PowerPoint slides. The results of this training show a significant improvement in students' competence in integrating multimedia into their presentations, which is expected to enhance the quality of presentations and the attractiveness of classroom learning.